Comparative study between high and low dose methylene blue infusion in septic cancer patients: a randomized, blinded, controlled study - Ehab Hanafy Shaker; Ahmed Mohamed Soliman; Ahmed Abd Elmohsen Bedewy; Mai Mohamed Elrawas (BMC Anesthesiology)
Abstract Purpose Septic shock is a common threat, and is the primary cause of death in almost all critical care units. Mortality of septic shock remains exceedingly high. The early use of methylene blue (MB) in different doses as adjunctive to vasopressors has promising results. Methods This double-blind, randomized, controlled trial comprised 90 patients divided into 3 groups: Group A received a 100 ml 0.9% NaCl placebo over 20 min; Group B received an MB bolus of 1 mg/kg in 100 ml 0.9% NaCl, and Group C received MB bolus of 4 mg/kg in 100 ml 0.9% NaCl during the same period. Groups B and C were given a 0.25 mg/kg/hour infusion of MB for 72 h after the bolus dose. All patients were started on noradrenaline at an infusion rate of 0.1–0.2 µ/kg/min and were adjusted accordingly to maintain MAP ≥ 65 mmHg. Time of vasopressor discontinuation was the primary outcome while total doses of vasopressors, ventilation days, vasopressors free days, total ICU stay, total hospital stay, and mortality rate were the secondary outcomes. Results Groups B and C exhibited significantly decreased time to vasopressor termination, and vasopressor-free days at 28 days in comparison to Group A. However, there was no significant difference between Groups B and C. Groups B and C had significantly lower noradrenaline dosages compared to Group A, however, no significant difference between Group B and Group C was found. The difference between the three groups in mortality rate was near statistical significance (p = 0.083). Using the logistic regression model, the 4 mg/kg group was protective against mortality with a hazard ratio of 0.29 (95%CI: 0.09–0.90). Conclusion In cancer patients with septic shock, early adjunctive MB delivery reduces the time to a vasopressor stoppage and increases the vasopressor-free days. No significant difference between high and low MB bolus doses, and no significant adverse effects were noted. Compared to placebo, the 4 mg/kg bolus dose shows a survival advantage. Trial registration Prospectively registered at clinicaltrials.gov [NCT 06005558]. (Date of registration 15/08/2023).